العينة وإشكالية التمثيل والتعميم في البحوث الاجتماعية والانسانية (مجلة الواحات للبحوث والدراسات, 2022)
ملخص    هدفت الدراسة إلى تناول العينة وإشكالية تمثيل المجتمع وتعميم النتائج في البحوث الاجتماعية والانسانية من خلال تعرض الباحث إلى تعريف كل من مجتمع البحث الأصلي والعينة البحثية ووحدة البحث، ثم تطرق إلى مبررات اللجوء إلى استخدام العينة عوض دراسة المجتمع ككل. وخطوات تصميم واختيار العينة، والعوامل التي تساعد الباحث على تحديد حجمها، كما تطرقنا ّإلى أهم أساليب العينات التي يستخدمها الباحثون في دراساتهم وابحاثهم الاجتماعية والانسانية التي تتمثل في أساليب العينات العشوائية واللاعشوائية. وأخيرا إلى الاتجاه نحو تحقيق التمثيل والتعميم في البحوث الاجتماعية والانسانية.    كلمات دالة: العينة, المجتمع الأصلي, البحوث الاجتماعية.     Abstract    The study aimed to address the sample and the problem of community representation and generalize the results in social and human research through the researcher's exposure to the definition of the original research community, the research sample, and the research unit, and then touched upon the justifications for resorting to using the sample instead of studying the community as a whole. And the steps of designing and selecting the sample, and the factors that help the researcher to determine its size, and we also touched upon the most important sampling methods that researchers use in their social and human studies and research, which are represented in the methods of random and non-random samples. Finally, there is a trend towards achieving representation and generalization in social and human research.    Key words: the sample; Native community; Social research.